Association of perceived food environment and obesity among school-aged children in selected barangays of San Pedro, Laguna - Baradi, Lousheil B.; Battung, Trishia Justine V.; Cacho, Ellana Francesca R.; Eduarte, Alessandro Gabriel D.; Ubante, Danica Anne A.; De Luna, Kim Leonard G.; Rodriguez, Anna Paulina S.
Obesity is an increasing global concern and is associated to a higher risk of non-communicable diseases. Despite their vulnerability, school-aged children (SAC) are often overlooked in nutrition research, even as their dietary intake and nutritional statuses are influenced by their food environments both at home and school. This study examined the association between perceived home and school food environments and obesity among SAC aged 10-12 in selected urban barangays of San Pedro, Laguna, Philippines. Specifically, it described the sociodemographic characteristics of SAC and their households, characterized the home and school food environments according to four key dimensions-affordability, availability, and acceptability-and assessed the association between PFE and the nutritional status of SAC.